Os determinantes do apoio à democracia nos países da América Latina - Celia Mara Ladeia Colen (2009)
This thesis was aimed at the analysis of the determinants of support for democracy in Latin America countries, based on Latinobarometer data - 2005. On theoretical grounding it have been taken over classical arguments of Culturalist Theory and Political Development Approach. Logistic Model and Multinomial Logistic Model were used to estimate thedeterminants of support. In order to test the various theoretical perspectives it have been included in the model the independent variables referred to Political Development Theory and Cultural and Institutional Approaches. Among the conclusions, it is detached that it is not possible to speak of a common political culture among the countries of Latin America, therefore, political support is dependent on the national context. Furthermore, the combination of the cultural, institutional and cognitive factors explain support for democracy in the region.The results show also the strength of the argument of Political Development Approach, according to which only the implementation of policies to reduce inequality and increase the aggregate capacity of the regime it will be possible to move forward in creating a reservoir ofsupport for democracy.